An impossible public problem or the paradox of activist resistance: Unwillingly depoliticizing immigrants’ schooling in France - Douniès, Thomas (Education Policy Analysis Archives, 2021)
In France as in other European countries, access to education for immigrants beyond compulsory schooling is selectively achieved, through a triage implemented by education administrations. Support organizations are increasingly solicited on this matter. Considering the twofold policy role of non-profits which both act as advocates and providers, this paper sheds light on the reciprocal relationship between the way activists manage enrollment in education and the way this issue is framed in the public sphere. Indeed, militants play a gatekeeping role and can discretely negotiate the access to school at the margins of the official institution. Nevertheless, because this struggle for education is individualized and silent, this issue is not likely to become a public and visible cause, around which a political reaction from public authorities could be claimed. Hence, while they largely counteract the infringement of the right to education, the actions of activists paradoxically participate in making it socially acceptable. That is why, beyond the case of immigrant education, the analysis eventually provides an empirical understanding of the social conditions of the construction of education public problems.